If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(x + -2) + 4(5n + -3) = -36 Reorder the terms: -6(-2 + x) + 4(5n + -3) = -36 (-2 * -6 + x * -6) + 4(5n + -3) = -36 (12 + -6x) + 4(5n + -3) = -36 Reorder the terms: 12 + -6x + 4(-3 + 5n) = -36 12 + -6x + (-3 * 4 + 5n * 4) = -36 12 + -6x + (-12 + 20n) = -36 Reorder the terms: 12 + -12 + 20n + -6x = -36 Combine like terms: 12 + -12 = 0 0 + 20n + -6x = -36 20n + -6x = -36 Solving 20n + -6x = -36 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6x' to each side of the equation. 20n + -6x + 6x = -36 + 6x Combine like terms: -6x + 6x = 0 20n + 0 = -36 + 6x 20n = -36 + 6x Divide each side by '20'. n = -1.8 + 0.3x Simplifying n = -1.8 + 0.3x
| 4(b+1)=-2(b+2) | | 8+x-1/x+4 | | -5-2(-6)=7 | | 49w^2-16w=0 | | 2x+3=-18+x | | 13b-6=3b+4 | | -2(-7k+5)+9=-13 | | 229-4x=32x+17 | | 1/9x^2+2/3x-3=0 | | 6-8x=114-29x | | x/5+x/7=8/7 | | 8(x+2)-2=22-4x-8+12x | | 5x+5=10x-20 | | 9x-5y=18 | | 12r^2=27+27r | | 2x+5=115-10x | | 12+2x=2-4x | | -4(t-1)+9t=8t-8 | | 6c^2+9c/3c | | -5(t-1)+7t=6t-6 | | n-14=16 | | 51-3x=10x+22 | | -5+6(x-3)=15x+3-9x | | -9(t+2)=54 | | 0.5x-0.3(10-3x)=-0.6(x-5) | | 13=13 | | 1/6x-3=5 | | -7/8v=35 | | 3+y/2=3y/4-2 | | x^2+10x+98=0 | | 6+6x=42+x | | -14-9=12 |